First detection of the pre-biotic molecule glycolonitrile (HOCH2CN) in the interstellar medium. (14th January 2019) - Zeng, S; Quénard, D; Jiménez-Serra, I; Martín-Pintado, J; Rivilla, V M; Testi, L; Martín-Doménech, R
ABSTRACT: Theories of a pre-RNA world suggest that glycolonitrile (HOCH2 CN) is a key species in the process of ribonucleotide assembly, which is considered as a molecular precursor of nucleic acids. In this Letter, we report the first detection of this pre-biotic molecule in the interstellar medium by using ALMA data obtained at frequencies between 86.5 GHz and 266.5 GHz toward the Solar-type protostar IRAS16293–2422 B. A total of 15 unblended transitions of HOCH2 CN were identified. Our analysis indicates the presence of a cold (T_ex = 24 ± 8 K) and a warm (T_ex = 158 ± 38 K) component meaning that this molecule is present in both the inner hot corino and the outer cold envelope of IRAS16293 B. The relative abundance with respect to H2 is (6.5 ± 0.6) × 10 −11 and ≥(6 ± 2) × 10 −10 for the warm and cold components, respectively. Our chemical modelling seems to underproduce the observed abundance for both the warm and cold component under various values of the cosmic ray ionization rate (ζ). Key gas phase routes for the formation of this molecule might be missing in our chemical network.